(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
This study investigated the influence of season and feeding regimes on the reproductive parameters of Kano Brown bucks. Forty-eight (48) bucks were utilized, with sixteen (16) bucks allocated to each of the three distinct seasons. The Kano Brown Bucks, a breed integral to Nigeria’s meat production industry, hold significant agricultural value, necessitating a deeper understanding of their reproductive physiology to optimize breeding strategies. Central to this is the concept of gonadal reserves, which pertain to sperm stored within the testes and serve as a critical indicator of fertility potential. These reserves, influenced by environmental and nutritional conditions, directly affect the breed’s reproductive capacity. Similarly, extra-gonadal reserves sperm stored in the epididymis and associated structures play a pivotal role in successful mating, underscoring the need to evaluate both reserves holistically. Seasonal variations, such as fluctuations between wet and dry seasons, introduce stressors that may disrupt hormonal balance and sperm production, while feeding regimes further modulate reproductive health, as balanced nutrition is essential for maintaining sperm quality and quantity. At the conclusion of the experimental period, twelve (12) bucks (three per treatment group) were orchidectomised. A total of twenty-four (24) testes (right and left) were harvested, and their weights (g) and lengths (cm) were recorded. Subsequently, the epididymis was meticulously dissected from each testis using a scalpel blade and further divided into its three anatomical regions: caput, corpus, and cauda epididymides. The weight (g) and length (cm) of each epididymal segment were also measured. Both testicular and epididymal tissues were processed in...